A Rare Case of Spontaneous Uterine Rupture in Second Trimester Pregnancy with Bicornuate Uterus: A Case Report - Eighty Mardiyan Kurniawati; Fadhilah Mega Indriati; Cholid Rochman Riskianto (Jurnal Ilmiah Kesehatan, 2022)
Eighteen weeks gestation of 34 years-old-woman with abdominal pain in the last 12 hours because of uterine rupture. Abdominal pregnancy was found with 2D ultrasound. On laparotomy exploration, bicornuate uterus was found with uterine rupture and an unviable fetus. Supravaginal hysterectomy was performed to control haemorrhage. Uterine anomaly is rare. However, the complications that occur will be an obstetric emergency. Screening uterine anomalies at premarital or early antenatal care is needed for predicting the risk of maternal mortality.